NbCl5-Promoted Synthesis of 4-Aryl-3,4-dihydrocoumarins by Multicomponent Reaction - dos Santos, Willian Henrique; da Silva-Filho, Luiz Carlos (Synthesis, 2012)
Substituted 4-aryl-3,4-dihydrocoumarins are synthesized from multicomponent reactions between phenols, dimethyl malonate, and aryl aldehydes catalyzed by niobium pentachloride. This new method is simple, cost-effective, and high-yielding, and can be conducted in acceptable reaction times.
Keywords: niobium pentachloride; multicomponent reaction; coumarin derivatives; Lewis acid; phenols